EKSISTENSI PERJANJIAN GALA (Gadai) TANAH PERTANIAN PADA MASYARAKAT ACEH DI KECAMATAN MEURAH MULIA KABUPATEN ACEH UTARA - MARSYUDDIN MARSYUDDIN (PREMISE LAW JURNAL, 2013)
ABSTRACT The life of community in rural areas is much different from that in urban areas. One of the differences is how to meet their financial needs. Unlike the rural community who has not known banking institution at all, when the people in the urban areas need money in a relatively big amount and are able to meet the requirements, they can send their application to the bank. Therefore, to meet the need for money in a relatively big amount whose coming could not be predicted, they used the mortgage institution available. Only with an agreement, somebody hands his productive land over to another party and in return he receives a certain sum of money in accordance with the agreement. If the land owner returns the amount of money, the land is returned to him/her. The problems to be solved in this study were the factors constituting the background for land mortgage agreement, the construction of land mortgage agreement, and how to pay and settle the land mortgage dispute in Acehnese community in Meurah Mulia Subdistrict, Aceh Utara District. Keywords: Land Mortgage Agreement, Adat, Aceh Utara.